HAK KOMPENSASI DENDA KETERLAMBATAN SESUAI PERJANJIAN PENGIKATAN JUAL BELI (PPJB) PERUMAHAN BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN NO 8 TAHUN 1999 (STUDI KASUS : PUTUSAN MA NO 930/PDT.SUS-BPSK/2016) - Avina Permatasari; Susanti Adi Nugroho (Jurnal Hukum Adigama, 2019)
In Indonesia, where one of the effects of globalization is high population growth rate, it proportionally correlates with housing development in major cities and its surrounding. House plays a mojor role in family development, a place to live safely and as a safe harbor for families where, the construction of the houses is usually done by the developer, especially in suburban areas. Both the developer and consumer have their own respective rights and obligation that has to be fulfilled as regulated by Consumer Protection Law Number 8 of 1999. The author raises the issue from the verdict of the Supreme Court No 930 regarding Special Civil Law of 2016 where the developer did not fulfill its obligation of finishing the construction on time and as a result, the consumer suing for her compensation right. The paper will address what legal protection method can a consumer get in order to fulfil their late compensation fees which included in Consumer Protection Law Number 8 of 1999? How the judge’s verdict of Supreme Court No 930 regarding Special Civil Law of 2016 impacting the case of the consumer versus the developer?